DAMPAK PENERAPAN PSAK 73 ATAS SEWA DAN IMPLEMENTASI PERPAJAKANNYA PADA PT. GARUDA INDONESIA, TBK - Sayid Ali Rahmad, Muhammad (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2023)
The application of PSAK 73 on leases is very important to know as a financial evaluation for a company in minimizing losses. Many companies say that the implementation of PSAK 73 in 2020-2021 causes an impact of a decline in equity to deepen, due to the recognition of the lessor's future debt. There are many practices of providing expensive fees, causing the company to experience difficulties. At the airline PT. Garuda Indonesia, the impact of this expensive rental fee has become an issue for PT Garuda Indonesia which greatly affects the company's finances. The research aims to review an impression of application of PSAK 73 about leases and an implementation of taxation at PT. Garuda Indonesia. This research was conducted on March-July 2022, where the research data is the 2021 financial statements. The mothod of this research used quantitative descriptive analysis. This research data is taken from an official website of companies listed on the Indonesia Stock Market. This reaserch results conclude the application of PSAK 73 will have the impression on the company's Statement of monetary Position by increasing the recognition of right-of-use assets and lease liabilities. However, the adoption of PSAK 73 doesn’t have a big impact on the company's profit or loss. Operating expenses on leases decreased, but depreciation expense and finance expenses increased as a result of the popularity of right-of-use assets and widowed-term liabilities. However, in the implementation of taxation, especially on PPh article 15 and PPh article 23 regarding rent, it actually has an impact on increasing company losses. This study indicates that it’s necessary to ensure the convenience of implementing PSAK 73 which has an effect on the company's accounting policies from the Indonesian Institute of Accountants.